Aplikasi Sistem Pendukung Keputusan Guru Terbaik Berdasarkan Kinerja dengan Metode Analytical Hierarchy Process (AHP) - Aulia Paramita; Fanisya Alva Mustika; Naely Farkhatin (Jurusan Sistem Informasi, Fakultas Teknologi Informasi, Universitas Andalas, 2017)
Abstract— Teacher is professional educator who have the duty, function, and important role in educating the nation. In order for the functions and duties inherent in the functional position of teacher conducted in accordance with the applicable rules, it is necessary to assess the performance of teacher who guarantee a quality learning process. Determine the performance of teacher can encourage an increase in the quality of education and increase motivation and professionalism of teacher in performing the tasks. The headmaster made 15 criteria to determine the best teacher, namely: attendance, discipline rules, responsibility and productivity, social interaction, motivation and self-development, innovative, responsive and initiative, flexibility in other tasks, communication, teamwork, honesty, friendly and polite, aesthetic dress, effective in using the gadget, cleanliness and tidiness class. To determine the performance of the teacher, then one decision that can be done using the Analytical Hierarchy Process (AHP). With the decision making is expected to choose an effective teacher performance. Determination of the teacher's performance is further processed by the criterium Decision Plus (CDP). The results of this study are the order of 4 of the best teachers at Yayasan Lentera Insan.